Area under the dark adaptation curve as a reliable alternate measure of dark adaptation response. Issue 10 (22nd April 2021) - Pundlik, Shrinivas; Nigalye, Archana; Laíns, Inês; Mendez, Kevin M; Katz, Raviv; Kim, Janice; Kim, Ivana K; Miller, John B; Vavvas, Demetrios; Miller, Joan W; Luo, Gang; Husain, Deeba
Abstract : Purpose: Quantification of dark adaptation (DA) response using the conventional rod intercept time (RIT) requires very long testing time and may not be measurable in the presence of impairments due to diseases such as age-related macular degeneration (AMD). The goal of this study was to investigate the advantages of using area under the DA curve (AUDAC) as an alternative to the conventional parameters to quantify DA response. Methods: Data on 136 eyes (AMD: 98, normal controls: 38) from an ongoing longitudinal study on AMD were used. DA was measured using the AdaptDx 20 min protocol. AUDAC was computed from the raw DA characteristic curve at different time points, including 6.5 min and 20 min (default). The presence of AMD in the given eye was predicted using a logistic regression model within the leave-one-out cross-validation framework, with DA response as the predictor while adjusting for age and gender. The DA response variable was either the AUDAC values computed at 6.5 min (AUDAC6.5) or at 20 min (AUDAC20) cut-off, or the conventional RIT. Results: AUDAC6.5 was strongly correlated with AUDAC20 (β=86, p<0.001, R 2 =0.87). The accuracy of predicting the presence of AMD using AUDAC20 was 76%, compared with 79% when using RIT, the current gold standard. In addition, when limiting AUDAC calculation to 6.5 min cut-off, the predictive accuracy of AUDAC6.5 was 80%. Conclusions: AUDAC can be a valuable measure to quantify the overall DA response and can potentially facilitate shorter testing duration while maintaining diagnostic accuracy.